The Effect of Implementation of Service Marketing Mix to the Process of Tourist Decision to Visit Tourism Object: A Case Study at Lembah Harau, Lima Puluh Kota Regency, Sumatera Barat Province, Indonesia - Rosha, Zeshasina; ., . (International Journal of Engineering and Technology, 2018)
This research examines the effect of product, price, place, promotion, people, process and physical evidence on touristsâ€™ decision process to visit the tourism object in Lembah Harau, Lima Puluh Kota Regency, Sumatera Barat Province, Indonesia. This tourism object consists of three resorts, namely Aka Barayun, Sarasah Bunta, and Rimbo Piobang. The approach in this research is a case study. The study population is tourists who visit the Lembah Harau. Primary data collected through a questionnaire. Data analysis was done by using a partial test (t-test). The result of the research revealed that product, place, promotion, and people significantly affects touristâ€™s decision process to visit Lembah Harau. Product variables have a dominant influence on the touristâ€™s decision. This proves that the object is the main consideration for tourists to visit the Lembah Harau, then sequentially followed by location, promotion, and people. Hence, not all aspects of the concept of the marketing mix influence the touristâ€™s decision process to visit the Lembah Harau attraction. Administrators of Lembah Harau are advised to maintain and develop products, easiness of process, fairness of the price, facilities, services, quality of people, and effective promotion strategy. Next researchers are recommended to study other tourist destinations in Sumatera Barat or continue this research by expanding the sample size and add other variables such as psychological factors and service quality.Â Â